2017
DOI: 10.1016/j.bpj.2017.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Acetylated Microtubules Are Preferentially Bundled Leading to Enhanced Kinesin-1 Motility

Abstract: The motor proteins kinesin and dynein transport organelles, mRNA, proteins, and signaling molecules along the microtubule cytoskeleton. In addition to serving as tracks for transport, the microtubule cytoskeleton directs intracellular trafficking by regulating the activity of motor proteins through the organization of the filament network, microtubule-associated proteins, and tubulin posttranslational modifications. However, it is not well understood how these factors influence motor motility, and in vitro ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
72
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 60 publications
5
72
0
1
Order By: Relevance
“…Biochemical experiments have shown that kinesin-1 selectively binds acetylated MTs; however, considering the lumen localization of K40, how this PTM influences kinesin binding is still unclear. It has been recently proposed that acetylated MTs, being enriched in high curve regions, can expose a greater number of available kinesin-binding sites and enhance kinesin run lengths [ 133 ].…”
Section: Neuronal Microtubules: Regulative Mechanismsmentioning
confidence: 99%
“…Biochemical experiments have shown that kinesin-1 selectively binds acetylated MTs; however, considering the lumen localization of K40, how this PTM influences kinesin binding is still unclear. It has been recently proposed that acetylated MTs, being enriched in high curve regions, can expose a greater number of available kinesin-binding sites and enhance kinesin run lengths [ 133 ].…”
Section: Neuronal Microtubules: Regulative Mechanismsmentioning
confidence: 99%
“…Ранее было продемонстрировано, что ацетилирование тубулина само по себе не влияет на скорость и длину пробега кинезина-1 вдоль МТ в системе in vitro [15], однако ацетилированные МТ предпочтительнее собираются в пучки, приводя к усилению подвижности этого транспортного белка [16]. Поэтому нам казалось логичным также проверить потенциальное влияние ацетилирования на взаимодействие α-тубулина с белком Atg8.…”
Section: результаты и обсуждениеunclassified
“…Depending on the cell type, MT networks are either unipolar, with all the MTs oriented in the same direction as in the vertebrate axons, or have mixed directionality as in vertebrate dendrites or epithelial cells [36][37][38][39][40][41]. Additionally, MTs form bundles, where several MTs are closely apposed, often connected by specialized cross-linking proteins [42][43][44], and unidirectional bundles facilitate intracellular transport [45,46]. On unidirectional networks, the overall outcome of transport is intuitive: towards the minus-or plus-ends depending on the motor type, however, this outcome is non-trivial in the case of MT networks with mixed directionality.…”
Section: Introductionmentioning
confidence: 99%